2020
DOI: 10.1038/s41398-020-00878-3
|View full text |Cite
|
Sign up to set email alerts
|

A key role of the subdiaphragmatic vagus nerve in the depression-like phenotype and abnormal composition of gut microbiota in mice after lipopolysaccharide administration

Abstract: The vagus nerve plays a role in the cross talk between the brain and gut microbiota, which could be involved in depression. The subdiaphragmatic vagus nerve serves as a major modulatory pathway between the brain and gut microbiota. Here, we investigated the effects of subdiaphragmatic vagotomy (SDV) on the depression-like phenotype and the abnormal composition of gut microbiota in mice after lipopolysaccharide (LPS) administration. LPS caused a depression-like phenotype, inflammation, increase in spleen weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 164 publications
(105 citation statements)
references
References 59 publications
(80 reference statements)
4
101
0
Order By: Relevance
“…The subdiaphragmatic vagus nerve serves as a major modulatory pathway between the brain and gut microbiota. Very recently, we demonstrated that lipopolysaccharide produces a depression-like phenotype and abnormal composition of gut microbiota via the subdiaphragmatic vagus nerve [38]. In this study, we found that the ingestion of L. intestinalis and L. reuteri did not induce depression-and anhedonia-like behaviors, increase plasma IL-6 levels, or reduce synaptic protein expression in the PFC in vagotomized mice.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The subdiaphragmatic vagus nerve serves as a major modulatory pathway between the brain and gut microbiota. Very recently, we demonstrated that lipopolysaccharide produces a depression-like phenotype and abnormal composition of gut microbiota via the subdiaphragmatic vagus nerve [38]. In this study, we found that the ingestion of L. intestinalis and L. reuteri did not induce depression-and anhedonia-like behaviors, increase plasma IL-6 levels, or reduce synaptic protein expression in the PFC in vagotomized mice.…”
Section: Discussionmentioning
confidence: 47%
“…1 c): Sham surgery or subdiaphragmatic vagotomy (SDV) was performed under anesthesia with 5% isoflurane. Mice were put under a microscope (Leica LEICA S9E, Germany), and hair was removed from the abdomen [ 38 ]. The esophagus of each mouse was exposed to the full view.…”
Section: Methodsmentioning
confidence: 99%
“…Collectively, our results suggest that gut microbiota composition alteration elicited by SD after sepsis plays key roles in the aggravation of systemic in ammation. It is evidenced that the communication between the brain and the endogenous and exogenous microorganisms in the gut could be modulated by the subdiaphragmatic vagus nerve [19,[43][44][45][46][47]. Our data showed that SDV abrogated post-septic SDmediated aggravation of systemic in ammation and multi-organ injuries.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies demonstrate that the ingestion of bene cial bacteria or selective serotonin reuptake inhibitors could alleviate stress-induced anxiety and depression-like behaviors via the subdiaphragmatic vagus nerve, which could be abolished by SDV [47,48]. We previously found that LPS at a dose of 0.5 mg/kg produces a depression-like phenotype and triggers in ammation via the subdiaphragmatic vagus nerve [19]. Abnormal composition of gut microbiota is observed after administration of 0.5 mg/kg LPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation